Dermacentor reticulatus is a vector of tick-borne encephalitis virus - Ličková, Martina; Fumačová Havlíková, Sabína; Sláviková, Monika; Slovák, Mirko; Drexler, Jan F.; Klempa, Boris (Ticks and tick-borne diseases, 2020)
Tick-borne encephalitis virus (TBEV; family Flaviviridae) is the most medically important tick-borne virus in Europe and Asia. Ixodes ricinus and I. persulcatus ticks are considered to be the main vector ticks of TBEV in nature due to their specific ecological associations with the vertebrate hosts. Nevertheless, recent TBEV prevalence studies in ticks suggest that Dermacentor reticulatus ticks might play a relevant role in the maintenance of TBEV in nature. The goal of this study was to evaluate the vector competency of D. reticulatus for TBEV through experimental tick infections and comparative in vivo transmission studies involving D. reticulatus and I. ricinus ticks. We observed that after a transcoxal micro-capillary inoculation, adult female D. reticulatus ticks efficiently replicated TBEV during the observed period of 21 days. The mean virus load reached up to 2.5 × 105 gene copies and 6.4 × 104 plaque forming units per tick. The infected D. reticulatus ticks were able to transmit the virus to mice. The course of infection in mice was comparable to the infection after a tick bite by I. ricinus while the virus spread and clearance was slightly faster. Moreover, D. reticulatus ticks were capable of tick-to-tick non-viraemic transmission of TBEV to the Haemaphysalis inermis nymphs during co-feeding on the same animal. The co-feeding transmission efficiency was overall slightly lower (up to 54 %) in comparison with I. ricinus (up to 94 %) and peaked 1 day later, at day 3. In conclusion, our study demonstrated that D. reticulatus is a biologically effective vector of TBEV. In line with the recent reports of its high TBEV prevalence in nature, our data indicate that in some endemic foci, D. reticulatus might be an underrecognized TBEV vector which contributes to the expansion of the TBEV endemic areas.